Analysis of heavy metal content (Pb, Cu, Cd, and Hg) on refilled drinking water in Malang City based on atomic absorption spectroscopy using the PCA method - Tazi, Imam; Margareta, Silvi Nadya; Chamidah, Ninik; Muthmainnah, Muthmainnah; Sasmitaninghidayah, Wiwis; Nadliriyah, Naqiibatin (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2025)
Refillable drinking water was chosen as an alternative to bottled drinking water because the price is cheaper. Drinking water has benefits for the body, but if the levels of heavy metals contained exceed the Ministry of Health's standards, it will have a negative impact on body health. This research was conducted with the aim of determining the quality of refillable drinking water in terms of heavy metal levels. Atomic absorption spectroscopy was used to test the levels of heavy metals (Pb, Cu, Cd, and Hg) in the samples. Research data shows that refill drinking water samples A1, A2, A3, A4 and A5 contain heavy metals at levels that exceed the Ministry of Health's standards. PC1 and PC2 have the highest eigenvalues, with a proportion of PC1 of 60.86% and PC2 of 22.69%. The two PCs have a cumulative proportion of 83.55% and are considered capable of representing the entire data. PCA method was used to identify patterns and group samples based on heavy metal content, with PC1 and PC2 reflecting 83.55% of the data variability. Pb and Cd are the variables that have the longest resultant lines, which shows that these two variables have a large contribution to the formation of new variables. The three secondary data samples, namely A6, A7, and A8, are control samples because their quality is good. Refill drinking water samples that are almost close to control are samples A1, A4, and A5, while samples A2 and A3 are far from control. The further the sample is from the control, the lower the quality. The results of this study highlight the need for strict supervision of refillable drinking water depots and the implementation of more effective purification methods to reduce heavy metal content exceeding health standards.